Chemical Profile of the Carpino Broad Bean by Conventional and Innovative Physicochemical Analyses. Issue 4 (25th June 2015) - Longobardi, F.; Sacco, D.; Casiello, G.; Ventrella, A.; Sacco, A.
Abstract A detailed chemical characterization of a typical Apulian legume, the Carpino broad bean, was obtained. Crude proteins, moisture, phosphorus, ash and energy content were evaluated on starting seeds, half‐ripening beans and final products. Stable isotope ratios (15N/14N and 13C/12C), major (Ca, Mg, Na and K) and trace metals (Zn, Mo, Mn, Cu, Fe, Cr, Cd, Ni and Co) were also assessed. Moreover, information on a large number of metabolites was obtained by 1H high‐resolution magic‐angle spinning nuclear magnetic resonance spectroscopy. The data revealed that Carpino broad bean dry seeds supply adequate protein and energy content, 28.1% and 326 kcal, respectively, being also a good source of macro‐ and microelements. In particular, the iron content was 46.0 mg/kg: this potentially provides about 33% of the recommended daily allowance by a 100 g serving. Moreover, the analyzed samples seem to lack elements considered potentially harmful for health. Practical Applications The Carpino broad bean is a native faba bean cultivar, traditionally cultivated in small quantities in Gargano (Southern Italy). It is commonly considered a traditional food product with interesting nutritional properties. At present, the Carpino broad bean has still not received an official European label as typical product, but it is a Slow Food presidium, this remarks its considerable socio‐cultural, nutritional and environmental values. Even if restricted to a limited geographic area, this typical and appreciable cultivation should be protected from extinction, preserving territory identity and working techniques; therefore, it is essential to explore ways to prove the Carpino broad bean quality and peculiarities, starting from a physicochemical characterization, that has not been presented in detail until now, and that could be a considerable basis for an official valorization of this product, for instance, for the attainment of EU Protected Designation of Origin/Protected Geographical Indication (EU PDO/PGI) labels.